Sistem Informasi Pengarsipan Surat Masuk dan Surat Keluar Berbasis Website pada PT. Zhanjiang Arta Kuopasific Indonesia - Nurul Masita; Nirsal; Vicky bin Djusmin (Ikatan Ahli Informatika Indonesia, 2024)
The purpose of this study is to design a website-based information system for archiving incoming and outgoing mail at PT. Zhanjiang Arta Kuopasific Indonesia. The type of research used is R&D (Research and Development) while the application development method used is the Rapid Application Development (RAD) method which consists of the planning phase, workshop design phase, and implementation phase. Data collection is done by observation, interviews, and literature studies. This website is designed using sublime text software, phpMyAdmin as a database, and the bootstrap 4 framework as css and javascript. Based on the results of black box testing, it states that the website system for archiving incoming and outgoing mail at PT. Zhanjiang Arta Kuopasific Indonesia can run well and produce results that are in accordance with expectations. This website is designed using the UML (Unified Modeling Language) modeling method consisting of use case diagrams, Activity diagrams, sequence diagrams and class diagrams. Based on the results of the web design validation given to 2 validators, the final score was 4.0, which means that the web design assessment is in the good category. Then from the results of the interface design validation given to 2 validators, the final score was 4.0, which means that the interface design assessment is in the strongly agree category. Furthermore, from the results of the UML validation given to 2 validators, the final score was 4.0, which means that the UML assessment is in the agree category. Then from the results of the database validation given to 2 validators, the final score was 4.0, which means that the database assessment is in the strongly agree category.